An investigation into factors affecting corporate risk management in ASEAN-4 Countries - Abdul Ghofar; Muhammad Muhammad; Amran Rasli; Dwi Narullia; Silvi Asna Prestianawati (Cogent Business & Management, 2022)
This study investigated the effect of corporate governance on corporate risk management. By using the regression analysis method, different results on the effects of the variables independent commissioners, female commissioners, meeting frequency, and audit committee members' expertise background on corporate risk management were obtained. In addition, companies in Singapore that had high levels of risk management activities were found to experience faster recovery after the crisis caused by the COVID-19 pandemic compared to other countries (Malaysia, Indonesia, and the Philippines). Overall, this study concludes that corporate governance has an important role in improving the risk management activities of a firm. This study may serve as a consideration for corporate governance implementation to improve corporate risk management.
Keywords: 650; Company Performance; COVID-19; Governance; Risk Management